Penanaman Pendidikan Karakter Kepada Siswa Melalui Program Kurangi Sampah Sekolah Kita “Kurasaki” (International Forum of Researchers and Lecturers, 2024)
This research aims to investigate the effect of instilling character education through our school's waste reduction program